Analisis Pengaruh Fungsi Perlombaan Desa terhadap Partisipasi Masyarakat dalam Pembangunan Desa di Kecamatan Teluk Mengkudu Kabupaten Serdang Bedagai - Naibaho, Manutur Parulian; Sihombing, Marlon; Tarmizi, Tarmizi (Universitas Negeri Medan, 2014)
The government faces quite big constrains in the implementation of rural development due to the aspects of Geography, Topology, Demography, infrastructure availability, poor human resources, and relatively low rural institutional capability. One of the very important attempts which needs to be carried out by Central Government and Local Government is to encourage, promote, develop and actualize the power and ability of the rural communities themselves. The power and ability sourced and found in the rural communities themselves is defined as âCommunity Participationâ. This studyÂ used the primary data obtained through interviewing the respondents (local community) and the secondary data obtained from the data of Subdistrict Government of Teluk Mengkudu, Statistic Coordinator of Teluk Mengkudu Subdistrict, Community Empowerment and Rural Government Board of Serdang Bedagai District. The result of this study showed that, based on the result of regression equation, the coefficient value of village competition was 0.6071 with sig.t = 0.000. Since the value of sig.t was < Î± (0.05), Ho was rejected and H1 was accepted. Thus, village competiton had a significant influence on the initiatives of the community in developing their village in Teluk Mengkudu Subdistrict. Then, from the other regression equation, it was found out that the coefficient value of village competition was 0.3278 with sig.t = 0.0156. Since the value of sig.t was < Î± (0.05), Ho was rejected and H1 was accepted. Thus, village competition had a significant influence on the active participation of the community in developing their village in Teluk Mengkudu Subdistrict. The positive sign of coefficient value of village competition showed that if Village Competition is increasingly enhanced, that intiative of the community in developing their village in Teluk Mengkudu Subdistrict is also increasingly increased or both variables had unidirectional relationship. The conclusion drawn from the result of this study is that Village Competition is one of the activities done by both Central Government and Local Government in theirn attempt to educate their people to increase their initiatives and active participation to develop their villages.